2011
DOI: 10.1016/j.ajog.2011.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Placental protein 13 (PP13/galectin-13) undergoes lipid raft-associated subcellular redistribution in the syncytiotrophoblast in preterm preeclampsia and HELLP syndrome

Abstract: Objective To investigate placental protein 13 (PP13) localization in relation to cytoskeleton and lipid rafts in preeclampsia and HELLP syndrome. Study Design Placental cryosections from patients with preeclampsia and HELLP, and controls were stained for PP13, actin, PLAP (lipid raft marker), and CD71 (nonraft marker). BeWo cells exposed to stress conditions were stained for PP13 and actin. Protein localization were investigated by confocal microscopy, PP13 concentrations by ELISA. Results PP13-actin coloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 98 publications
8
80
0
Order By: Relevance
“…After mid-gestation, serum PP13 levels sharply rise in women who enter the active phase of the pathology due to shedding of syncytiotrophoblast microparticles from damaged placental villi [13,14,19,22,32]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After mid-gestation, serum PP13 levels sharply rise in women who enter the active phase of the pathology due to shedding of syncytiotrophoblast microparticles from damaged placental villi [13,14,19,22,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has been shown that PP13 may act as a marker to predict preeclampsia already in the first trimester of pregnancy. PP13 is secreted from the syncytiotrophoblast after week 5 of gestation, either as single molecule or via shedding of syncytial microparticles [12,13,19]. Therefore, PP13 has been proposed as a specific biomarker and a promising tool to predict preeclampsia in early pregnancy [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein, also known as galectin 13, is exclusively produced in the syncytiotrophoblast layer of the placenta, from where it reaches the maternal blood circulation from as early as the 6 th week of gestation [3,17]. In singleton pregnancies, lower first trimester levels of PP13 can be used, together with other markers, for predicting an individual woman's risk of developing preeclampsia (PE) [14,17,18,26].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy pregnancy, serum PP13 concentrations rise moderately from the first to the third trimester [20]. However, lower first-trimester levels of maternal serum PP13 [12,25,26] and its encoding mRNA [27,28] have been shown not only in cases developing early-onset preeclampsia, but also in those patients developing a severe form of late-onset preeclampsia [13,20]. PP13 has therefore been proposed as a specific biomarker for predicting preeclampsia in early pregnancy [13,23,25,26].…”
Section: Introductionmentioning
confidence: 99%